Courses
Courses for Kids
Free study material
Offline Centres
More

# Find the sum of all even natural numbers from 2 to 40

Last updated date: 28th Feb 2024
Total views: 360.6k
Views today: 6.60k
Verified
360.6k+ views
Hint: To solve this question, firstly we will find the number of even number from 2 to 40 by using formula of finding ${{n}^{th}}$ term of an A.P when last term is given. After finding the value of n, we will find the summation of those n terms by taking a = 2 and l = 40, where a is the first term of an A.P and l is last term of an A.P.

Before solving this question, we must know about Natural Numbers and Even Numbers.
Natural numbers are those that are used for counting and ordering.
Example: 1, 2, 3, 4, 5……….100, 117, 674, 123, etc.
Any integer that can be divided exactly by 2 is an even number. The last digit of even numbers is 0, 2, 4, 6 or 8, i.e. the digits ending with 0, 2, 4, 6 or 8 are always divisible by 2 and thus, are even numbers.
Example: 26, 18, 20456, 2716, 2756, 204, etc. are all even numbers because they are divisible by 2.
To solve this question we will simply add the first natural numbers that are even from 2 to 40.
Let us now solve the question.
The even natural numbers from 2 to 40 are: 2, 4, 6, 8, 10, 12, 14, 16, 18, 20, 22, 24, 26, 28, 30, 32, 34, 36, 38 and 40.
We know that, ${{n}^{th}}$ term of an A.P when last term is given can be find by formula $l=a+(n-1)d$, where $l={{a}_{n}}$
As, l = 40 and a = 2
So, $40=2+(n-1)2$
On simplifying, we get
$38=(n-1)2$
$(n-1)=19$
n = 20
so, there are a total of 20 even numbers from 2 to 40.
Now, we know that the sum of terms of an arithmetic progression which as follows
${{S}_{n}}=\dfrac{n}{2}\left( a+l \right)$ , where $l=a+(n-1)d$.
So, putting values of l, a, n and d, we get
${{S}_{20}}=\dfrac{20}{2}\left( 2+40 \right)$
On simplifying, we get
${{S}_{20}}=10\times 42$
Or, ${{S}_{20}}=420$
Hence, the sum of all even natural numbers from 2 to 40 is equals to 420.

Note: One must always know that ${{n}^{th}}$ term of an A.P is given can be find by formula ${{a}_{n}}=a+(n-1)d$, also, remember that the sum of terms of an arithmetic progression which as follow${{S}_{n}}=\dfrac{n}{2}\left( 2a+(n-1)d \right)$, where a = first term of an A.P, n = total number of terms of an A.P and d=common difference between consecutive terms in an A.P. Try not to make any calculation mistake.